Our contemporary Oscar Liera:: A Critique of Late Twentieth-Century Authoritarianism - Velázquez Hernández, Santos Javier (2022)
This article approaches three "political" plays by playwright Óscar Liera, El jinete de la Divina Providencia (1985), Los caminos solos (1987) and Camino rojo a Sabaiba (1988), from a cultural history perspective. Based on the concept of "representation", we study how the author created a social identity through his works, interviews, and public letters, to confront to authoritarianism of the State in the eighties in Mexico. Through the genre of farce, with topics such as social justice, political corruption or cacicazgo, he set out to create citizenship in the spectator/reader. His works are the positioning of an intellectual in the public space, and whose ethical resistance is indispensable even in the scenario of Latin American democracy.